Weight Change Two Years after the Termination of the Intensive Lifestyle Intervention in the Look AHEAD Study - Chao, Ariana M (Obesity (Silver Spring), 2020)
OBJECTIVE: To evaluate weight changes after cessation of the 10-year intensive lifestyle intervention (ILI) in the Look AHEAD (Action for Health in Diabetes) study. We hypothesized that ILI participants would be more likely to gain weight during the 2-year observational period following termination of weight-loss-maintenance counseling than would participants in the Diabetes Support and Education (DSE) control group. METHODS: Look AHEAD was an RCT that compared the effects of ILI and DSE on cardiovascular morbidity and mortality in participants with overweight/obesity and type 2 diabetes. Look AHEAD was converted to an observational study in September 2012. RESULTS: Two years after the EOI, ILI and DSE participants lost a mean±SE of 1.2±0.2 kg and 1.8±0.2 kg, respectively (p=0.003). Thirty-one percent of ILI and 23.9% of DSE participants gained ≥2% (p<0.001) of EOI weight, while 36.3% and 45.9% of the two groups, respectively, lost ≥2% of EOI weight (p=0.001). Two years after the EOI, ILI participants reported greater use of weight-control behaviors than DSE participants. CONCLUSIONS: Both groups lost weight during the 2-year follow-up period, but more ILI than DSE participants gained ≥2% of EOI weight. Further understanding is needed of factors that affected long-term weight change in both groups. CLINICAL TRIALS REGISTRATION: NCT00017953